Uberlegungen zur Alterität und Modernität der mittelhochdeutschen Dichtung - Greenfield, John (1996)
In this article, which is the revised and shortened text of a public lecture given at the University of Porto in April 1996, the author, using as a starting point JAUSS' essay on "Alteritat und Modernitat der mittelalterlichen Literatur" discusses the ways in which we have viewed Middle High German lyric love poetry, the Nibelungenlied and Wolfram's Parzival and Willehalm.